EVALUASI KEBIJAKAN PENINGKATAN KESIAPSIAGAAN MASYARAKAT KOTA PADANG DALAM MENGHADAPI BENCANA GEMPABUMI DAN TSUNAMI - Rahmadian Novert (Yogyakarta State University, 2015)
The purpose of this research is to evaluate and examine government Padang City efforts in improving the preparedness of community as a form of disaster risk reduction efforts the earthquake and tsunami. This research was conducted with descriptive method with the qualitative approach. The results of this research shows that there are 2 categories of the efforts made by Government of Padang city in enhancing preparedness community. First: increasing the Community Capacity by providing the knowledge and understanding of disaster that spelled out into action disaster preparedness curriculum integration into the formal education curriculum, disasters, simulated socializing and community empowerment through the formation of disaster preparedness in every village. Second: provision support facilities preparedness communities, by setting policy, the creation of operational Guidelines in case of an emergency and evacuation facilities development, as well as early warning facilities. However the majority of the program made still are incidental and not in a sustainable way. The existence of restructuring and its frequent mutations in the BPBDPK body, the lack of availability of budget related preparedness, as well as the presence of apathy from the community is the bearer of three factors in an attempt to increase preparedness conducted the government of Padang City.Keyword: Evaluation, Preparedness, the Role of Local Government